INOVASI PENINGKATAN PELAYANAN PARKIR MELALUI PENGGUNAAN MEMBER DAN UANG ELEKTRONIK DI UIN SYARIF HIDAYATULLAH JAKARTA - Rahman, Habibur; Muzaki, Farid; Ilmi, Dahrul (Sharia Faculty of State Islamic Institute (IAIN) Palangka Raya, 2023)
This article discusses the problem of large queues at the student parking exit, because the majority of the UIN Syarif Hidayatullah academic community uses both two-wheeled and four-wheeled vehicles, so they need a parking area to park their vehicles and to control vehicles. The current parking space at UIN Syarif Hidayatullah, namely the parking area next to the UIN Syarif Hidayatullah Jakarta Public Library, is insufficient. So the UIN Syarif Hidayatullah Jakarta campus uses a dual payment system. Electronic parking system (E-Parking) and also taking steps to create an electronic parking system (E-Parking) using member cards for employees and electronic money (E-Money) for students to overcome traffic jams at the exit. This research was conducted using qualitative research methods, where this research was carried out by understanding the phenomena that occurred at UIN Syarif Hidayatullah Jakarta, or observations made by the author within the UIN Syarif Hidayatullah Jakarta environment. The sources used for this research method are observation, interviews and documentation. The results of the research show that to solve the traffic jams that often occur in the UIN Syarif Hidayatullah Jakarta area when students enter the campus area or leave the campus, the campus provides a solution, namely the innovation of implementing electronic parking (E-Parking) in the hope of reducing the number of traffic jams. which occurred in the UIN Syarif Hidayatullah Jakarta area. The use of electronic parking is not a solution to reduce congestion in the UIN Syarif Hidayatullah Jakarta area because considering the limited parking space provided by UIN Syarif Hidayatullah Jakarta for parking, it would not be able to accommodate vehicles brought by students. Therefore, there are several solutions to make the UIN Jakarta parking area better, one of which is: 1. Adding more space for parking 2. Students are prohibited from bringing vehicles in the UIN Syarif Hidayatullah Jakarta area 3. Adding counters at the exit.